Characteristics of certain types of control over the activities of higher educational institutions of Ukraine - О. О. Avdieiev (Law and Safety)
The types of control over the activities of higher education institutions of Ukraine have been studied and generalized. The concept of "type of control" and "form of control" have been distinguished. The essence and features of the procedure of state control over the activities of higher education institutions of Ukraine depending on its type have been described, the classification of types of control has been carried out and shortcomings outlined.